2011
DOI: 10.1007/s12070-011-0333-4
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis of Larynx Revisited: a Report on Clinical Characteristics in 10 Cases

Abstract: Tuberculosis is the most frequent granulomatous disease involving larynx. In most cases it is secondary to pulmonary tuberculosis. Incidence of tuberculosis is now on a rise due to increase in incidence of immune deficiency states. Here we present a report of clinical characteristic of laryngeal tuberculosis based on our experience of 10 cases. A detailed retrospective analysis of 10 patients of laryngeal tuberculosis was done at our tertiary care laryngology centre. Majority of patients had change of voice an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
2
14
0
Order By: Relevance
“…The anatomical and voice disorders of LTB patients were analyzed. There was prevalence of adult males, as already described in literature [ 1 , 7 , 8 , 9 ].The vocal fold was the most involved anatomical site and dysphonia the most frequent symptom, consistent with other studies [ 7 , 8 , 9 ]. All the patients with lesions in the vocal folds reported dysphonia.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The anatomical and voice disorders of LTB patients were analyzed. There was prevalence of adult males, as already described in literature [ 1 , 7 , 8 , 9 ].The vocal fold was the most involved anatomical site and dysphonia the most frequent symptom, consistent with other studies [ 7 , 8 , 9 ]. All the patients with lesions in the vocal folds reported dysphonia.…”
Section: Discussionmentioning
confidence: 64%
“…Laryngeal tuberculosis (LTB) is the most frequent larynx granulomatous disease. In general there is lung involvement but in an important proportion of cases you can find LTB without pulmonary disease[ 1 , 7 , 8 , 9 ]. The lesions observed in LTB, such as ulceration and fibrosis can interfere in the process of voice production [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common symptom of laryngeal tuberculosis is hoarseness or change of voice. 4,5 However, in our case the patient presented to us with odynophagia with no change in voice. Laryngeal tuberculosis can be primary or secondary.…”
Section: Discussionmentioning
confidence: 54%
“…11 Recent studies have shown that laryngeal TB is rarely associated with active pulmonary TB suggesting that the mode of transmission may be due to direct laryngeal seeding of aerosolized bacilli confirming a recent shift in the clinical and pathophysiology of the condition. 2,12,13 It is reported that laryngeal TB occurs with a lesser degree of pulmonary involvement. With non-specific lesions, there is less chance of pulmonary involvement, but with ulcerative and granulomatous lesions there is a greater chance of pulmonary involvement 4 and our patient had simple congestion with fine granularity on endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…It remains the most common ENT manifestation of TB, commonly involves the larynx from pulmonary lesions, but rarely it involves the larynx by a primary affection from inhaled tubercle bacilli. 2 The natural history of laryngeal TB has changed over the time. The age group of patients being affected by this is on the rise from young adults earlier to elderly people with a male predominance, which is especially marked in patients >50 years of age.…”
Section: Introductionmentioning
confidence: 99%